Jumping performance variability in young elite gymnasts - Marina, M.; Busquets, A.; Rodriguez, F. A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Young gymnasts under the age of 13 have shown a greater capacity to reproduce vertical jump performance on a contact platform using the counter-movement jumping (CMJ) technique (5,3%<CV<7,3%), as compared with a pre-pubertal, non-gymnastic population (Viitasalo 1988). The same study reports a lower inter-subject variability (CV=4,6%) in subjects older than 15 years of age, as well as increasing variability with increasing loads. This observation was explained by higher variability in neuromuscular reponse as children increase their power output. Ishii et al. (1983) have shown that maximal jumping efficiency (about 30%) is not reached until the age of 17. On the other hand, Martin et al. (2001) observed good repeatibility of basic vertical jumps (SJ, CMJ, CMJA with arms action) in non-athletic children 6 to 8 years old (CCI.0.95). The aim of this study was to establish jumping performance variability and reliability in pre-pubertal elite gymnasts. Methods 58 female and 57 male national elite gymnasts, 8 to 12 years of age, were grouped into two age categories (8-10 and 11-12 years) in a cross-sectional design. Subjects in the first group trained 12 to 15 h/week, whereas subjects in 11-12 group trained 15 to 18 h/week. They all performed a battery of drop jump tests (DJ) from 20, 40, 60, 80, and 100 cm. All subjects made two trials at each drop height. A contact platform (Bosco-Ergojump, Italy) was used to measure flight time (FT, ms). Inter-trial and intra-subject stability were measured using three different statistical indices: linear product-moment correlation coefficient (r), intraclass correlation coefficient (ICC), and coefficient of variation (CV, %). Gymnasts of both genders have shown a very stable individual performance in DJ from all drop heights (0.85<ICC<0.99; p.0.0001). This observation is confirmed by the high correlation between the first and second trial (0.76<r<0.99). The higher level of repeatibility between trials (ICC, r) in the younger gymnasts (8-10 years) as compared with the older group (11-12 years) is highlighted. The low CV among both males (2.80%<CV<4.96%) and females (2.14%<CV<4.66%) points out an acceptable inter-individual variability and, with only isolated exceptions, it is higher among gymnasts under 10 years of age. Reliability parameters are comparable in both genders across the age span and do not show any clear differential trend. Discussion/Conclusion These results show a good reliability of vertical jumping performance among elite gymnasts already at very young ages (8-12 years). Interestingly, this applies to pliometric jumps, which have been proposed as the most relevant aspect of jumping performance in gymnastics (Marina & Rodriguez 1996). These results also support previous observations in which gymnasts showed higher jumping performance stability (4.6<CV<7.1%; Viitasalo 1988) as compared with a large sample of non-athletic subjects of similar age (8.3<CV<11.8%; ICC>0.95) (Martin et al. 2001). We have hypothesized that this higher jumping performance stability in gymnasts is related to their high training volume already from very young ages and the large amount of pliometric jumps included in their training routines.